Comparative socio-economic analysis of manual and mechanized transplantation method of spring rice (Oryza sativa) production in Chitwan, Nepal - Thapa, Garima; Kunwar, Yanjal (Archives of Agriculture and Environmental Science, 2025)
This study aimed to assess and compare the socioeconomic aspects of mechanized and manual transplantation methods in spring rice production. A survey was conducted in 2024 through pre-tested interview schedules and Key Informant Interviews (KIIs) to collect primary data, while secondary data were collected from relevant publications. A total of 90 farmers (45 using manual transplantation and 45 using mechanized transplantation) were selected through simple random sampling from two purposively chosen municipalities. Among the respondents, 51.1% continued using the traditional manual transplantation method, while 48.9% adopted the mechanized transplantation method, citing cost-effectiveness as a key factor. Similarly, 36.69% of labour cost was accounted for total cost of production in manual transplantation method whereas only 23.45% of labour cost was accounted for total cost of production in mechanized transplantation method. The average gross margin per hectare in mechanized transplantation method (NPR 93325.25/ USD 681.58) was higher than the manual transplantation method (NPR 64654.561/ USD 472.19). Using mechanized transplantation method was more profitable (BCR: 1.76) than using manual transplantation method (BCR: 1.50) in spring rice production. The findings indicated that mechanized transplantation method significantly (p<0.05 reduces dependence on labour and enhances profitability in spring rice production. Therefore, I creased promotion of mechanization, along with policy measures and access to appropriate machinery, could reverse the productivity decline and improve the economic resilience of rice farmers in Chitwan, Nepal.